Shared and Distinctive Ultrastructural Abnormalities Expressed by Megakaryocytes in Bone Marrow and Spleen From Patients With Myelofibrosis - Zingariello, Maria; Rosti, Vittorio; Vannucchi, Alessandro M.; Guglielmelli, Paola; Mazzarini, Maria; Barosi, Giovanni; Genova, Maria Luisa; Migliaccio, Anna Rita (Frontiers in Oncology, 2020)
Numerous studies have documented ultrastructural abnormalities in malignant megakaryocytes from bone marrow (BM) of myelofibrosis patients but the morphology of these cells in spleen, an important extramedullary site in this disease, was not investigated as yet. By transmission-electron microscopy, we compared the ultrastructural features of megakaryocytes from BM and spleen of myelofibrosis patients and healthy controls. The number of megakaryocytes was markedly increased in both BM and spleen. However, while most of BM megakaryocytes are immature, those from spleen appear mature with well-developed demarcation membrane systems (DMS) and platelet territories and are surrounded by platelets. In BM megakaryocytes, paucity of DMS is associated with plasma (thick with protrusions) and nuclear (dilated with large pores) membrane abnormalities and presence of numerous glycosomes, suggesting a skewed metabolism toward insoluble polyglucosan accumulation. By contrast, the membranes of the megakaryocytes from the spleen were normal but these cells show mitochondria with reduced crests, suggesting deficient aerobic energy-metabolism. These distinctive morphological features suggest that malignant megakaryocytes from BM and spleen express distinctive metabolic impairments that may play different roles in the pathogenesis of myelofibrosis.